Peran Orang Tua dalam Membimbing Anak dalam Pembelajaran Daring di Era New Normal - Devi Fitriani (IAIN Kendari, 2022)
This qualitative descriptive study aims to determine the role of parents in the learning process of children in the new normal era, to examine how children respond to treatments/actions that are made by parents when online learning is carried out. The research data were obtained using interview, observation, and documentation instruments. The data was then analyzed through several stages, namely data reduction, data presentation, and drawing conclusions. The validity of the research data was tested by using source and time triangulation techniques. The results showed that the model of parental guidance for children when learning online was parents as directors, acting as facilitators, motivators, and mentors for children. Some children perceive the presence of their parents beside them to ease the child's work in understanding the material given by the teacher. However, some of the other children thought that parents only restrained their children from studying and did not give them the freedom to learn.Keywords: Online learning, parents’ role, student’s perception